2009
DOI: 10.1369/jhc.2009.954594
|View full text |Cite
|
Sign up to set email alerts
|

Genomic, Tissue Expression, and Protein Characterization of pCLCA1, a Putative Modulator of Cystic Fibrosis in the Pig

Abstract: Recent studies have identified members of the CLCA (chloride channels, calcium-activated) gene family as potential modulators of the cystic fibrosis (CF) phenotype, but differences between the human and murine CLCA genes and proteins may limit the use of murine CF models. Recently established pig models of CF are expected to mimic the human disease more closely than the available mouse models do. Here, we characterized the porcine CLCA gene locus, analyzed the expression pattern and protein processing of pCLCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 19 publications
(65 citation statements)
references
References 57 publications
3
62
0
Order By: Relevance
“…Gradient gel electrophoresis using Novex Ò 4-20% Tris-glycine gel 1.0 mm (Invitrogen) was performed to better differentiate between similarly sized bands but failed to improve the resolution on the blots (not shown). Immunoprecipitation of mCLCA5 transfected HEK293 cells was performed as described previously (Plog et al 2009). Unfortunately, all antibodies failed to detect any specific band in the immunoblot after immunoprecipitation (data not shown).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gradient gel electrophoresis using Novex Ò 4-20% Tris-glycine gel 1.0 mm (Invitrogen) was performed to better differentiate between similarly sized bands but failed to improve the resolution on the blots (not shown). Immunoprecipitation of mCLCA5 transfected HEK293 cells was performed as described previously (Plog et al 2009). Unfortunately, all antibodies failed to detect any specific band in the immunoblot after immunoprecipitation (data not shown).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…For example, mCLCA3, its human ortholog hCLCA1, the equine ortholog eCLCA1 and the porcine ortholog pCLCA1 are expressed in goblet cells only (Anton et al 2005;Gruber et al 1998;Plog et al 2009), whereas mCLCA6 is exclusively expressed in nongoblet cell enterocytes (Bothe et al 2008). In contrast, more complex and partly contradictory expression patterns have been reported for several other CLCA family members, such as hCLCA2 (Agnel et al 1999;Connon et al 2005;Pauli et al 2000) and its murine ortholog mCLCA5 (Beckley et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In each species analyzed to date, four to eight CLCA family members are predominantly expressed on the surfaces of mucous membranes and the skin (Braun et al, 2010;Loewen and Forsyth, 2005;Patel et al, 2009;Plog et al, 2009). All CLCA proteins are post-translationally cleaved into two subunits (Patel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the pCFTR signals obtained from goblet cells are clearly located between the nucleus and porcine goblet cell granule marker pCLCA1 (Plog et al 2009). Unfortunately, no other antibodies were identified that could serve for co-localization studies of pCFTR with specific subcellular structures, mostly due to their lack of crossreactivity on pig tissues (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…Analysis of the pCFTR mRNA Tissue Expression Pattern Total RNA was isolated from tissues as described previously (Plog et al 2009). PCR primers were designed using the Beacon Designer 3.0 software (Premier Biosoft International; Palo Alto, CA) and are listed in Table 1.…”
Section: Animals and Tissue Processingmentioning
confidence: 99%